COVID-19 and cardiothoracic surgery: A risk-adjusted approach in the context of a global pandemic - Reddy, Darshan; Kleinloog, Robert; Janson, Jacques; Manganyi, Rogers; Brink, Johan; Zilla, Peter (SA Heart Journal, 2020)
In the face of the novel coronavirus pandemic, the impact of COVID-19 infection has disrupted cardiothoracic surgical services globally. A risk-adjusted approach to restructuring the delivery of cardiothoracic surgical services has been proposed in accordance with international guidance to ensure that the surgical standard of care is maintained in the practice of adult and paediatric cardiac surgery, as well as thoracic surgery. The potential influx of COVID-19 patients with cardio-respiratory complications requiring intensive care management and associated surgical procedures falling within the gamut of the thoracic surgeon, is considered. Finally, the protection of healthcare workers, in particular the surgical team exposed to aerosolising procedures, is outlined.